Pendekatan Pembelajaran Berbasis Perubahan Sosial untuk Mendukung Keberlanjutan Lingkungan dan Pemberdayaan Masyarakat di Kecamatan Sukamakmur - Jaenal Mutakim; Oong Komar; Elih Sudiapermana; Joni Rahmat Pramudia; Lenny Nuraeni (Postgraduate, University of Mataram, 2025)
This research aims to develop a social change-based learning approach that supports environmental sustainability and community empowerment in Sukamakmur District, Bogor Regency. The region faces challenges related to social inequality and environmental degradation caused by urbanization and socio-economic changes. A mixed-methods approach was used, utilizing quantitative analysis through Exploratory Factor Analysis (EFA) to identify the factors influencing social change, along with in-depth interviews to explore the needs and potential of community-based learning. The results show that social equality and social innovation are key factors driving change, while ideological conservatism is the main obstacle. The designed learning strategies, such as blended learning and project-based learning (PBL), focus on improving community skills in natural resource management, environmental literacy, and the adoption of environmentally friendly technologies. This approach effectively encourages the active participation of the community in maintaining the balance of the ecosystem while improving their quality of life. This research contributes to the development of sustainable, inclusive, and adaptive learning practices and serves as a guide in designing learning programs that are relevant to the needs of the community. These findings are expected to be the basis for implementing educational strategies that encourage social transformation, community empowerment, and environmental conservation in the future.